Nature for Mental Health and Social Inclusion - Bishop, Benjamin P. (Disability Studies Quarterly, 2012)
In the United States there remains an effort for mental health services to provide holistic options that improve symptomatology while improving social belonging for people diagnosed with serious and persistent mental illnesses. Consequently, the mental healthcare delivery system appears to create community-situated users of services rather than people who are active members of their communities. This article reports on literature associated with the use of horticulture and gardening for mental health recovery and embraces the use of these services to generate enduring and genuine community integration outcomes through professional-community relationships. Conclusions are that mental health services should engage Nature-related programing to provide opportunities that enhance multiple aspects of health and well-being, increase constructive interpersonal relationships that lead to a more authentic social inclusion, and support the destigmatization of mental illnesses. Keywords: mental health; integration; Nature, gardening, social and therapeutic horticulture; eco-therapy